Analisis Kesulitan Belajar Matematika Siswa Kelas Tinggi dalam Menyelesaikan Soal Cerita pada Meteri Bangun Datar - Debby Yuliana Sinaga; Grace Tessalonika Juliarta; Sarah Sihombing; Sonia Sonia; Chintya Saragi; Monalisa Sion Siallagan; Jelita Septri Ananda Siahaan; Mahatma Mahatma; Leo Samri Simanjuntak (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
This study aims to analyze students' mathematical learning difficulties based on high (KMT), medium (KMS), and low (KMR) ability levels. Results revealed that KMT subjects demonstrated strong conceptual understanding but struggled with contextual comprehension of problems. KMS subjects could grasp concepts well but faced challenges in applying formulas to contextual problems. Meanwhile, KMR subjects experienced significant difficulties in understanding concepts, applying formulas, and solving contextual problems altogether. The study highlights the importance of implementing instructional strategies focused on strengthening conceptual understanding and contextual problem-solving to enhance students' skills.